Muscari baeticum (Scilloideae, Asparagaceae), a new addition to the native flora of Tunisia and third report to Mediterranean Africa - El Mokni, Ridha (Hacquetia, 2022)
Muscari baeticum, originating from western Europe, is here recorded as new from the central eastern part of Tunisia. So far, it was known only from Algeria and Morocco within the southern part of the Mediterranean basin. Description of the species as well as first data about its ecology in Tunisia together with geographical distribution and diagnostic features of closely related species are given. Photographic illustrations of the new reported taxon and an updated key to the Muscari species in North Africa are also provided.